PENDIDIKAN DI ERA REVOLUSI INDUSTRI 5.0 - Arjunaita, Arjunaita (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The Industrial Revolution 5.0 has brought changes in various aspects of human life. Among these is the education system. The question is, what components of education are affected, and how to respond to these implications? This paper aims to explain the changes that must be made in schools so that human resources produced by various educational institutions can compete and contribute globally. Through literature review and content analysis, the discussion shows that current and future curriculum development must complement students' abilities in the academic dimension, life skills, live together, and think critically and creatively. Other invisible skills like interpersonal skills, global-minded citizens, and literacy of the media and information available. The curriculum must also be able to shape students with an emphasis on the STEM field, referring to ICT-based learning, the internet of things, big data and computers, as well as entrepreneurship and internships. The competencies that must be possessed by teachers are educational competence, competence for technological commercialization, competence in globalization, competence in future strategies, and competence counselor. In addition to these competencies, teachers also need to have a friendly attitude with technology, collaboration, be creative and take risks, have a good sense of humor, and teach holistically. Schools and teachers must consider the open learning platform in deciding how to organizing education and learning             Keywords— Education 5.0, Industry 5.0, Blended learning, Teacher competence, Century skill Abstrak— Makalah ini bertujuan untuk menjelaskan perubahan yang harus dilakukan di sekolah sehingga sumber daya manusia yang dihasilkan oleh berbagai lembaga pendidikan dapat bersaing dan berkontribusi secara global. Melalui kajian literatur dan analisis isi, penulis menjelaskan bahwa pengembangan kurikulum saat ini dan di masa depan harus melengkapi kemampuan siswa dalam dimensi akademik, keterampilan hidup, kemampuan untuk hidup bersama dan berpikir secara kritis dan kreatif. Keterampilan tak kasat mata seperti keterampilan interpersonal, berpikir global, dan literasi media dan informasi. Kurikulum juga harus dapat membentuk siswa dengan penekanan pada bidang STEM, merujuk pada pembelajaran berbasis TIK, internet of things, big data dan komputer, serta kewirausahaan dan magang. Selain guru memiliki kompetensi mengajar dan mendidik, literasi media, competence in globalization, competence in future strategies, dan konseling, juga perlu memiliki sikap ramah teknologi, kolaborasi, menjadi kreatif dan mengambil risiko, memiliki selera humor yang baik, serta mengajar secara holistik. Sekolah dan guru perlu mempertimbangkan pembelajaran terbuka dan daring dalam memutuskan bagaimana menyelenggarakan pendidikan dan pembelajaran.   Kata Kunci— Pendidikan 5.0, Industri 5.0, Kompetensi guru, Pembelajaran, Kemampuan Siswa